1982
DOI: 10.1172/jci110531
|View full text |Cite
|
Sign up to set email alerts
|

Role of alpha-macroglobulin-elastase complexes in the pathogenesis of elastase-induced emphysema in hamsters.

Abstract: A B S T R A C T Radiolabeled, enzymatically active or chloromethyl ketone-inactivated porcine pancreatic elastase was endotracheally instilled into hamsters. Gel filtration of the bronchopulmonary lavage fluid revealed two major radioactive fractions: one, eluting at 780,000 daltons, corresponding to an a-macroglobulinpancreatic elastase complex, and another, at 68,000 daltons, corresponding to an a-1-protease inhibitorpancreatic elastase complex. Elastolytic activity was recovered in the bronchopulmonary lava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
1

Year Published

1983
1983
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 29 publications
1
29
1
Order By: Relevance
“…3). Indeed, active A2M:NE complexes have been implicated in the pathogenesis of emphysema in animal models (48), the adult respiratory distress syndrome in humans (56), and the degradation of cartilage matrix in rheumatoid arthritis (30). Our data (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…3). Indeed, active A2M:NE complexes have been implicated in the pathogenesis of emphysema in animal models (48), the adult respiratory distress syndrome in humans (56), and the degradation of cartilage matrix in rheumatoid arthritis (30). Our data (Fig.…”
Section: Discussionmentioning
confidence: 52%
“…a-2-Macroglobulin physically entraps enzymatically active elastase and sterically blocks the proteolytic activity of elastase towards all substrates over 8,500 D, including a-l-PI (64). Complexes ofa-2-macroglobulin and elastase are rapidly cleared from the circulation, but Stone and co-workers (64,65) have reported that complexes trapped in connective tissues can propogate additional damage after the slow release of active elastase from degraded a-2-macroglobulin. Thus, the oxidatively linked shunting of elastase from a-1-PI to a-2-macroglobulin may mediate either anti-or proinflammatory effects depending on the rate of clearance of the complex.…”
Section: Discussionmentioning
confidence: 99%
“…a-I-AP and alpha-2-macroglobulin are the two serum factors that inhibit the effects of elastase. It has been suggested that alpha-2-macroglobulin does not fully inhibit the destructive action of elastase (32). That a-I-AP is the prime elastase inhibitor is supported by the finding that congenital deficiency of this inhibitor is associated with emphysema.…”
Section: Discussionmentioning
confidence: 99%